2020
DOI: 10.21203/rs.2.24005/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum Fetuin-A levels are increased and associated with insulin resistance in  women with polycystic ovary syndrome

Abstract: Background: Insulin resistance (IR) is a common characteristic of women with polycystic ovary syndrome (PCOS). It has been reported that circulating Fetuin-A levels were associated with IR and type 2 diabetes mellitus (T2DM). However, previous reports were inconsistent.Methods: 207 subjects were screened for PCOS according to the diagnostic guideline of the Rotterdam consensus criterion. Serum Fetuin-A levels were measured using an ELISA kit. An independent t-test or Nonparametric test was used to detect diffe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The results also showed a significant increase in the level of Fetuin-A in women with PCOS, and that the cause of the rise may be attributed to metabolic disorders resulting from hyperandrogenism and hyperinsulinemia, which may enhance the synthesis and release of Fetuin-A in vivo, in addition to, the increase in Fetuin-A can be derived at least in part from the low-grade inflammatory state, in which inflammatory cytokines such as CRP are increased in women with PCOS (21) . The lipid concentrations (TC, TG, HDL-C, LDL-C, VLDL) were estimated in the blood sera of PCOS and healthy women, and the mean ± standard deviation of lipids was shown in Table (2).…”
Section: Level Of Serum Fetuin-amentioning
confidence: 94%
“…The results also showed a significant increase in the level of Fetuin-A in women with PCOS, and that the cause of the rise may be attributed to metabolic disorders resulting from hyperandrogenism and hyperinsulinemia, which may enhance the synthesis and release of Fetuin-A in vivo, in addition to, the increase in Fetuin-A can be derived at least in part from the low-grade inflammatory state, in which inflammatory cytokines such as CRP are increased in women with PCOS (21) . The lipid concentrations (TC, TG, HDL-C, LDL-C, VLDL) were estimated in the blood sera of PCOS and healthy women, and the mean ± standard deviation of lipids was shown in Table (2).…”
Section: Level Of Serum Fetuin-amentioning
confidence: 94%
“…Previous studies have shown differences in circulating levels of endocrine FGFs ( 13 , 14 ) and fetuin-A ( 15 ) in PCOS women. FsGF21 and fetuin-A were reported to be elevated and FGF19 was found to be lower in PCOS women compared to healthy controls ( 13 15 ).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown differences in circulating levels of endocrine FGFs ( 13 , 14 ) and fetuin-A ( 15 ) in PCOS women. FsGF21 and fetuin-A were reported to be elevated and FGF19 was found to be lower in PCOS women compared to healthy controls ( 13 15 ). Acute intralipid administration elevates circulating free fatty acid (FFA) and triglycerides, decreases peripheral glucose uptake resulting in increased insulin resistance ( 16 18 ).…”
Section: Introductionmentioning
confidence: 95%